2022
DOI: 10.1364/ao.454801
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the spectral response of a division-of-focal-plane polarization imager using a grating monochromator

Abstract: Spectral characterizations are performed on imagers to obtain a relative spectral response (RSR) curve. This process often utilizes a grating monochromator with an output that changes polarization as a function of wavelength (our monochromator’s degree of linear polarization was found to vary from less than 10% to more than 70%). When characterizing a polarization-sensitive imager, this introduces polarization artifacts into the RSR curve. We present a simple method to avoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…2, according to the process described in previous work. 9 The monochrome camera was used with a near infrared (NIR) filter for one experiment. The spectral transmission of this filter was measured with an integrating sphere and a spectrometer.…”
Section: Instruments and Methodologymentioning
confidence: 99%
“…2, according to the process described in previous work. 9 The monochrome camera was used with a near infrared (NIR) filter for one experiment. The spectral transmission of this filter was measured with an integrating sphere and a spectrometer.…”
Section: Instruments and Methodologymentioning
confidence: 99%
“…The gain, or "ISO" setting as defined in the Raspberry Pi documentation, was held at a value of 1 for all measurements; however, the exposure time, or "Shutter Speed", setting of the cameras was governed by the output power of the monochromator. Since the output power of the monochromator varied with wavelength, 45 the exposure time required adjustment across the wide spectral range to maintain ample signal. This variation in the exposure time of the images was accounted for by relying on the linear relationship that has been shown to exist 46 between the exposure time and signal such that a pixel multiplier could be applied to each image based on the exposure time.…”
Section: Relative Spectral Response Characterizationmentioning
confidence: 99%
“…Polarimetric corrections were performed with each imaging system on the camera. The relative spectral response of the detector was also measured using a grating monochromator, 13 and the detector had a response from 400 to 1000 nm.…”
Section: Imaging System Characterizationsmentioning
confidence: 99%
“…We previously found that the horizontally polarized subpixels on the detector have polarizers with a higher transmission than the vertically polarized subpixels, which causes images to have a bias towards horizontal polarization. 13 For the 300-mm lens system, the system matrix developed in the polarimetric calibration corrects both sources of error. For the telescope, we expected the first type of error to be very small, since an f/10 Schmidt-Cassegrain telescope design is symmetric about the axis with weakly curved surfaces.…”
Section: Imaging System Characterizationsmentioning
confidence: 99%